COVID-19 and the CPI - Reinsdorf, Marshall B. (International Monetary Fund, 2020)
COVID-19 changed consumers' spending patterns, making the CPI weights suddenly obsolete. In most regions, adjusting the CPI weights to account for the changes in spending patterns increases the estimate of inflation over the early months of the pandemic. Under-weighting of rising food prices and over-weighting of falling transport prices are the main causes of the underestimation of inflation. Updated CPI weights should be developed as soon as is feasible, but flux in spending patterns during the pandemic complicates the development as quickly as 2021 of weights that represent post-pandemic spending patterns
10.5089/9781513560281.001
Keywords: Graue Literatur; Business and Economics; Health and Fitness; Diseases: Contagious; Index Numbers and Aggregation; leading indicators; Price Level; Deflation; Health Behavior; Industry Studies: Transportation and Utilities: General; Economic Development: Urban; Rural; Regional; and Transportation Analysis; Infrastructure; Macroeconomics; Infectious & contagious diseases; Consumer price indexes; COVID-19; Inflation; Transportation; Housing; Health; National accounts; Price indexes; Communicable diseases; Prices; Saving and investment; inflation measurement; Consumer Price Index; CPI